The Virtual Axle concept for detection of localised damage using Bridge Weigh-in-Motion data. (15th April 2015) - Cantero, Daniel; Karoumi, Raid; González, Arturo
Graphical abstract: Highlights: New output-only level I damage detection technique for short span road bridges. New use of Bridge Weigh-in-Motion (B-WIM) technology. Proposed damaged indicator based on introduction of a fictitious weightless axle. Better performance than monitoring changes in natural frequencies. Abstract: This paper proposes a new level I damage identification method for short span statically indeterminate bridges using the information provided by a Bridge Weigh-in-Motion system. Bridge Weigh-in-Motion systems measure the bridge deformation due to the crossing of traffic to estimate traffic attributes, namely axle weights and distances between axles for each vehicle. It is theoretically shown that it is convenient to introduce a fictitious weightless axle, which has been termed 'Virtual Axle', in the Bridge Weigh-in-Motion calculations to derive a damage indicator. The latter can be used both as a new robust output-only model-free level I Structural Health Monitoring technique and as a new self-calibration method for Bridge Weigh-in-Motion systems. The response of a fixed-fixed beam traversed by a 2-axle vehicle travelling over an irregular profile is used to validate the proposed method. By means of Monte Carlo simulation the influence of the key parameters such as the degree and location of damage, noise levels, span lengths and profile irregularities on the accuracy of the method are investigated. The results show that the 'Virtual Axle' method is able to detect small local damages in statically indeterminate structures.